Thermal Stability of EVA Nanocomposites for Solar Cell Encapsulation - Ganiyu Olamide Ogunsiji; Oluwaseyi Omotayo Alabi; Adeoti Oyegbori Laoye; Saidat Abisoye Salisu; Samuel Adekunle Dada (PT. Teknologi Futuristik Indonesia, 2026)
The long-term reliability and performance of photovoltaic (PV) modules largely depend on the thermal stability and durability of encapsulation materials that protect solar cells from environmental and thermal degradation. Ethylene–vinyl acetate (EVA) is widely used as a solar cell encapsulant due to its excellent optical and mechanical properties; however, its thermal stability and resistance to degradation remain critical challenges under prolonged operating conditions. Although EVA-based nanocomposites have been investigated for solar cell encapsulation, limited studies have systematically examined how different nanoclay fillers and processing conditions influence the thermal stability and encapsulation efficiency of EVA materials. This study aims to optimize the thermal stability of EVA nanocomposites by incorporating different inorganic fillers mica, montmorillonite (MMT), and vermiculite, at varying concentrations and milling cycles. An 8% EVA solution was prepared and blended with these fillers to evaluate their effects on the thermal and structural properties of the nanocomposite materials. Thermal characterization using Differential Scanning Calorimetry (DSC) and Thermogravimetric Analysis (TGA) revealed noticeable changes in melting temperature, glass transition temperature, and thermal degradation behavior. The incorporation of nanofillers improved the thermal stability of the EVA matrix and influenced its crystallinity and mechanical properties. The optimized EVA nanocomposite demonstrated enhanced thermal resistance and improved durability compared with neat EVA, although a slight reduction in encapsulation efficiency was observed. These findings provide valuable insights into the formulation and optimization of EVA nanocomposites for solar cell encapsulation, contributing to the development of more thermally stable and durable encapsulation materials for sustainable photovoltaic applications.